2010
DOI: 10.1088/0953-8984/22/8/084010
|View full text |Cite
|
Sign up to set email alerts
|

Towards hot electron mediated charge exchange in hyperthermal energy ion–surface interactions

Abstract: We have made Na (+) and He (+) ions incident on the surface of solid state tunnel junctions and measured the energy loss due to atomic displacement and electronic excitations. Each tunnel junction consists of an ultrathin film metal-oxide-semiconductor device which can be biased to create a band of hot electrons useful for driving chemical reactions at surfaces. Using the binary collision approximation and a nonadiabatic model that takes into account the time-varying nature of the ion-surface interaction, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The ability to electronically activate a surface chemical reaction using a solid-state device is a concept with important implications for chemical processing and energy conversion and has been the goal of considerable research. ,,, A number of attempts have been made to achieve this goal using a metal–insulator–metal device as a tunnel junction. This type of device allows for the emission of hot electrons with tunable energy from one metal layer to the other. If the cathode layer of the device is sufficiently thin, then the emitted electrons may reach the surface before thermalizing.…”
Section: Influence Of Hot Electrons On Surface Chemistry and Heteroge...mentioning
confidence: 99%
“…The ability to electronically activate a surface chemical reaction using a solid-state device is a concept with important implications for chemical processing and energy conversion and has been the goal of considerable research. ,,, A number of attempts have been made to achieve this goal using a metal–insulator–metal device as a tunnel junction. This type of device allows for the emission of hot electrons with tunable energy from one metal layer to the other. If the cathode layer of the device is sufficiently thin, then the emitted electrons may reach the surface before thermalizing.…”
Section: Influence Of Hot Electrons On Surface Chemistry and Heteroge...mentioning
confidence: 99%
“…Regarding the effects of the interaction of ions and GNPs on the heating effects, the energy transfer between an ionic object and GNPs can be in the form of a photon, 33,34 which however lies in the UV range; or via collision between high energy ions and GNPs, 35,36 which is not possible for this study since an alternating RF field cannot accelerate ions constantly. In our experiment, the main heating effect is contributed from the conductivity change, as shown in Fig.…”
Section: 23mentioning
confidence: 99%
“…The goal of activating nonthermal chemical processes electronically using a solid-state device is an active area of research, and attempts to drive nonthermal surface chemistry have focused primarily on using a tunneling junction to emit hot electrons into a metal thin film. , When the thickness of the metal thin film is less than the mean free path of the hot electron, it is assumed that the electron reaches the surface before scattering to low energy electron hole pairs and subsequent lattice vibrations (a process that occurs in ∼1 ps) . Several studies have demonstrated the ability of these hot electron emitters to induce a chemical reaction involving a single preadsorbed monolayer of reactant. However, no reports have been made that demonstrate the ability to electronically activate a catalyst operating in steady state turnover by directly measuring the product yield.…”
mentioning
confidence: 99%